Association between pelvic floor muscle strength and sexual function based on PISQ-12—an analysis of data from a multicenter cross-sectional study on 735 nulliparae during pregnancy - Gao, Lei; Xie, Bing; Zhu, Hongmei; Zhang, Di; Fu, Xiuhong; Li, Hongjuan; Zhen, Min; Qin, Baoling; Chen, Weipeng; Mao, Xuying; Kong, Lingrui; Wang, Jianliu; et al. (Frontiers in Medicine, 2023)
Background: Pelvic floor muscle strength is well-known associated with female sexual function. But there were a few studies reported the relationship in pregnant women and present results were inconsistent. Nulliparae is a specific cohort with simplicity to exclude confounding factors caused by parity. The study aimed to explore the association of pelvic floor muscle strength and sexual function based on Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) of nulliparae during pregnancy. Methods: This is a second analysis of the baseline data from a randomized controlled trial which aimed to study the protective efficacy of pelvic floor muscle training on stress urinary incontinence at 6th week postpartum (registration number: ChiCTR2000029618). Nulliparae aged 20-40 years old with singleton pregnancy before 16 weeks of gestation enrolled, and data including participants’ demographic information, the Modified Oxford Scale (MOS) and PISQ-12 were collected. Eligible nulliparae were divided into two groups: Group MOS > 3 and Group MOS ≤ 3. Demographic information of two groups was compared. Sexual function based on PISQ-12 scores of two groups were compared. Comparison of PISQ-12 scores between two groups is calculated by Mann–Whitney U test using SPSS version 23.0. Results: 735 eligible nulliparae were enrolled in this study. Along with MOS grading up, PISQ-12 scores tended to get lower. There were 378 and 357 participants were included in Group MOS > 3 and Group MOS ≤ 3, respectively. The PISQ-12 scores of Group MOS > 3 is significantly lower than Group MOS ≤ 3 (11 vs. 12, p<0.001). The scores of the frequency of feeling sexual desire, orgasm achievement, sexual excitement, sexual activity satisfaction, the sexual intercourse pain, fear of urinary incontinence and negative emotion reactions with sexual intercourse of Group MOS > 3 is lower than Group MOS ≤ 3 (p<0.05). Conclusion: Pelvic floor muscle strength is positively associated with sexual function based on questionnaire of young nulliparae during their first trimester. Up to half of nulliparae during the first trimester are suffering weak pelvic floor muscle strength and nearly a quarter of nulliparae combine with sexual dysfunction.